2017
DOI: 10.5812/iranjradiol.63463
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Carcinoma Arising in Microglandular Adenosis of the Breast: A Case Report and Literature Review

Abstract: Microglandular adenosis is an uncommon, benign breast disease considered to be a variant of adenosis. Breast carcinoma arising in microglandular adenosis has been reported. Because of its extreme rarity, its clinical and radiological features are not well known. We present a case of invasive carcinoma arising in microglandular adenosis of the breast in a 63-year-old woman with radiologic and pathologic findings. To our knowledge, this is the first case report with breast magnetic resonance imaging findings tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The latter showed a lobulated, heterogeneous hypoechoic mass on US. Oh et al [ 21 ] have reported one case of invasive carcinoma arising in MGA. Mammogram showed an irregular isodense mass with a spiculated margin and irregular hypoechoic mass in US examination.…”
Section: Discussionmentioning
confidence: 99%
“…The latter showed a lobulated, heterogeneous hypoechoic mass on US. Oh et al [ 21 ] have reported one case of invasive carcinoma arising in MGA. Mammogram showed an irregular isodense mass with a spiculated margin and irregular hypoechoic mass in US examination.…”
Section: Discussionmentioning
confidence: 99%
“…No specific predisposing factors have been identified. MGA is often an incidental finding but may present as a mammographic density or calcifications [2][3][4][5][6]. MGA is often inconspicuous on gross examination though it has been described as a poorly defined nodularity or mass.…”
Section: Introductionmentioning
confidence: 99%
“…The benign areas of the tumor will show strong positivity for S-100 whereas invasive areas will have patchy positivity for S-100 immunohistochemical stain. 1,8 Both benign and malignant tumors of breast can be the differential diagnosis of microglandular adenosis.…”
mentioning
confidence: 99%